Lack of adequate seed supply is a major bottleneck for effective ecosystem restoration in Chile: friendly amendment to Bannister et al. (2018). Issue 2 (5th February 2020) - León‐Lobos, Pedro; Bustamante‐Sánchez, Marcela A.; Nelson, Cara R.; Alarcón, Diego; Hasbún, Rodrigo; Way, Michael; Pritchard, Hugh W.; Armesto, Juan J.
Abstract : We argue that the need for a quality seed supply chain is a major bottleneck for the restoration of Chile's native ecosystems, thus supplementing the list of bottlenecks proposed by Bannister et al. in 2018. Specifically, there is a need for defining seed transfer zones, developing standards and capacities for properly collecting and storing seeds, reducing information gaps on seed physiology and longevity, and implementing an efficient seed supply chain with certification of seed origin and quality. Without such capacities, countries are unlikely to meet their restoration commitments. Although we focus on bottlenecks in Chile, the issues we raise are relevant to other countries and thus the global agenda for ecological restoration.